β-Catenin transcriptional activity is required for establishment of inner pillar cell identity during cochlear development. - Michael Ebeid; Ippei Kishimoto; Pooja Roy; Mohd Ali Abbas Zaidi; Alan G Cheng; Sung-Ho Huh (PLoS Genetics, 2023)
The mammalian cochlea is composed of sensory hair cells as well as multiple different types of non-sensory supporting cells. Pillar cells are one type of supporting cell that form the tunnel of Corti and include two morphologically and functionally distinct subtypes: inner pillar cells (IPCs) and outer pillar cells (OPCs). The processes of specification and differentiation of inner versus outer pillar cells are still unclear. Here, we show that β-Catenin is required for establishing IPC identity in the mammalian cochlea. To differentiate the transcriptional and adhesion roles of β-Catenin in establishing IPC identity, we examined two different models of β-Catenin deletion; one that deletes both transcriptional and structural functions and one which retains cell adhesion function but lacks transcriptional function. Here, we show that cochleae lacking β-Catenin transcriptional function lost IPCs and displayed extranumerary OPCs, indicating its requirement for establishing IPC identity. Overexpression of β-Catenin induced proliferation within IPCs but not ectopic IPCs. Single-cell transcriptomes of supporting cells lacking β-Catenin transcriptional function show a loss of the IPC and gain of OPC signatures. Finally, targeted deletion of β-Catenin in IPCs also led to the loss of IPC identity, indicating a cell autonomous role of β-Catenin in establishing IPC identity. As IPCs have the capacity to regenerate sensory hair cells in the postnatal cochlea, our results will aid in future IPC-based hair cell regeneration strategies.